Molecular aspects of vitamin d anticancer activity - Picotto, Gabriela (2012)
Environment may influence the development and prevention of cancer. Calcitriol has been associated with calcium homeostasis regulation. Many epidemiological, biochemical, and genetic studies have shown non-classic effects of vitamin D, such as its involvement in the progression of different cancers. Although vitamin D induces cellular arrest, triggers apoptotic pathways, inhibits angiogenesis, and alters cellular adhesion, the precise mechanisms of its action are still not completely established. This article will present a revision about the molecular aspects proposed to be involved in the anticancer action of calcitriol. Adequate levels of vitamin D to prevent cancer development will also be discussed.